KOMPOSISI DAN STRUKTUR VEGETASI PAKAN JULANG SULAWESI (Rhyticeros cassidix) DI DAERAH ALIRAN SUNGAI (DAS) MARISA KABUPATEN POHUWATO - Sidik Katili , Abubakar; Podungge, Sandra; J. Lamangantjo, Chairunnisah; Ahmad, Jusna; Susanti Hamidun, Marini; Zakaria, Zuliyanto (Universitas Cokroaminoto Palopo, 2024)
The Sulawesi hornbill (Rhyticeros cassidix) is a Sulawesi endemic that is under threat of extinction. The Sulawesi Hornbill (Rhyticeros cassidix) inhabits the area of Popayato-Paguat, particularly the Marisa River Basin near Karangetang Village. The goal of this study is to establish the composition and structure of the vegetation around the Sulawesi Hornbill nesting habitat, particularly in the Marisa River Basin. The method employed was field observation, namely Vegetation Analysis. Direct observation was used to obtain data, with three stations established. The square survey collected data for tree level in a 20 × 20 m plot, pole level in a 10 x 10 m plot, stake level in a 5 x 5 m plot, and seedling level in a 2 x 2 m plot. The research findings revealed the composition of vegetation for the Sulawesi Hornbill's food in the Marisa Watershed Forest of Karangetang Village, which consists of 8 species of vegetation for the Sulawesi Hornbill, namely Aglaia argentea (Matowa), Livistona rotundifolia (Woka/Fan Palm), Madhuca pilphinenis (Flowering Wood/Camphor), Palaquium javense (Palapi), Ficus nervosa (Banyan), Dracontomelon dao (Dao), Pterospermum celebicum. The vegetation structure of the Sulawesi hornbill’s food in the Marisa River Basin Forest area of Karangetang Village shows the highest Important Value Index (IVI) for trees is Ficus nervosa (87.83%), for poles is Madhuca pilphinenis (85.45%), for stakes is Aglaia